Pemberian Posisi Semi Fowler Meningkatkan Saturasi Oksigen Pasien PPOK - Ni Made Dwi Yunica Astriani; Putu Wahyu Sri Juniantari Sandy; Made Mahaguna Putra; Mochamad Heri (Journal of Telenursing (JOTING), 2021)
This study aims to determine the effectiveness of the Semi Fowler position on oxygen saturation in COPD patients. The research design used the One Group Pre-Post Test Design. The research results on 30 COPD respondents showed that the average value of oxygen saturation before being given the Semi Fowler position was 89.47. After being given the Semi Fowler position for 30 minutes, the average oxygen saturation value of COPD patients increased, namely 95.83. The results of the paired t-test show that the results are sig (2-tailed) or the value of r = 0.0001. In conclusion, there is an increase in the oxygen saturation values after being given the Semi Fowler position. Keywords: COPD, Oxygen Saturation, Semi Fowler